Factors that may influence polymorphous low-grade adenocarcinoma growth - Soares, Andresa Borges; Martinez, Elizabeth Ferreira; Avila Ribeiro, Patricia Fernandes; Barreto, Icleia Siqueira; Aguiar, Maria Cassia; Furuse, Cristiane [UNESP]; Sperandio, Marcelo; Montalli, Victor Angelo; Araujo, Ney Soares de; Araujo, Vera Cavalcanti de (Springer, 2017)
There is mounting evidence on the importance of some biological processes in tumor growth, such as vascular supply, apoptosis, autophagy, and senescence. We have investigated these processes in polymorphous low-grade adenocarcinoma (PLGA), in an attempt to identify those that are relevant for this particular lesion. We analyzed 31 cases of PLGA using immunohistochemistry to antibodies against CD34 and CD105 to detect blood vessels; against D2-40 to detect lymphatic vessels; against Bax, Bcl-2, and survivin to explore cell apoptosis; and against Beclin and LCB3 to investigate autophagy and against p21 and p16 to assess senescence. Our results showed that PLGA growth does not depend on newly formed vessels but only on preexisting vasculature. Furthermore, PLGA is promoted by autophagy, sustained by both anti-apoptotic and anti-senescence signals, and stimulated by Bcl-2 and survivin.
Keywords: Polymorphous low-grade adenocarcinoma; Angiogenesis; Apoptosis; Autophagy; Senescence; Bcl2; Survivin; LC3B